Pengaruh Manajemen Kurikulum Terhadap Peningkatan Kinerja Guru - Mila Amelia; Sulastia; Doni Adriansyah; Merika Setiawati; Nikmah Hayati (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
Curriculum management plays a crucial role in enhancing teacher performance, ultimately contributing to the overall quality of education. Based on various sources, effective curriculum management encompasses planning, implementation, organization, and evaluation of the curriculum. Proper implementation of these aspects has been proven to positively influence teacher performance, both partially and simultaneously. Research indicates that curriculum management can improve teachers' abilities in managing learning, understanding student characteristics, and applying diverse teaching strategies. Additionally, teacher commitment and pedagogical competence are significant supporting factors. The combination of optimal curriculum management and professional teacher performance can enhance student learning outcomes and overall educational quality.